Adaptive thermal comfort in the offices of North-East India in autumn season - Singh, Manoj Kumar; Ooka, Ryozo; Rijal, Hom B.; Takasu, Marina (Building and environment, 2017)
India has a large diversity in climate, socio-cultural setup, and economy, but it aims to provide better amenities and shelter to all by 2022. India is also progressing on the path of high-energy efficiency in the building sector to reduce the energy usage in this sector. In India, decisions are generally made based on energy efficiency as the sole criterion, a fact that holds true for the built environment as well. Studies have shown that a more balanced approach is ‘Adaptive thermal comfort’, which integrates the subject's thermal preferences in the thermal environment, where a subject will experience optimum comfort for most of the time. The climate of North-East India as well as the construction and operation of office buildings is quite different compared to the rest of India. Questionnaire-based field surveys were done in naturally ventilated office buildings at two locations in North-East India (Tezpur and Shillong) in autumn season (September to November 2016). A total of 460 subjects (Tezpur: 295; Shillong: 165) voluntarily participated in this study. Nonlinear regression analysis shows clothing related adaptation by subjects at low and high temperatures, but the maximum adaptation takes place on the cooler side of the thermal sensation scale. Griffiths and linear regression analysis shows that the comfort temperature is 27.3 °C. However, the preferred temperature is 24.5 °C, that is, 2.8 °C lower than the comfort temperature. Logistic regression analysis shows that ∼50% of the fans are operating in offices at 31 °C and almost no fan is in use up to 22.5 °C. •Study assesses thermal comfort in the offices of North-East India in autumn season.•All the offices considered in the study are naturally ventilated.•Griffiths and linear regression analysis shows that comfort temperature is 27.3 °C.•Preferred temperature in the offices is 24.5 °C i.e. 2.8 °C lower than comfort temperature.•Logistic regression analysis shows that at 31 °C about 50% fans in the offices are operating.